Optimizing Effect of Wavy Leading Edge (WLE) in Rectangular Wing and Taper Wing - Iis Rohmawati; Hiroshi Arai; Hidemi Mutsuda; Takuji Nakashima; Rizal Mahmud (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2021)
Experimental and numerical research have been performed to investigate the Wavy Leading Edge (WLE) effect on the rectangular wing. The WLE is inspired by humpback whale flipper morphology which is blunt and rounded in certain form pattern. This flipper shape plays an important role for its behaviour specially capturing their prey. This advantage could be applied to other systems such as fin stabilizers or wind turbines. Steady cases in various aspect ratios were conducted to find out the optimum effect of WLE with baseline NACA 0018 profile at Reynolds number 1.4 x 105. The chord length of the wing (c) was 125 mm. The WLE shape defined as wavelength (W) 8% of c and amplitude (d) is 5% of c. The aspect ratio (AR) variations were 1.6; 3.9; 5.1; 7.9 and 9.6.Â A simple rectangular form of the wing was selected to analysis the WLE effect on the various ARs. The taper wing shape is applied to find out the WLE effect at the AR 7.9. three types of taper ratio (TR) are 0.1; 0.3 and 0.5. The results show that the WLE on the taper wing has better advantage to control the stall in steady case. Another impressive result was the WLE wing with AR 7.9 and TR 0.3 has the best lift coefficient and pressure distribution.Keywords: stall, wavy leading edge, steady case, rectangle wing, taper wing, aspect ratio.Â